INGLIZ VA OʻZBEK TILLАRIDА “OILА” KONSEPTINI IFODALOVCHI FRАZEOLOGIK BIRLIKLАRNING QIYOSIY-LINGVOMADANIY TАHLILI - Komilov Shukurullo Abdurashidovich; N.N. Radjapov (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This article presents a comparative linguocultural analysis of phraseological units conveying the concept of “family” in English and Uzbek. Drawing on the frameworks of cognitive linguistics and phraseology, the study examines family-related idioms, proverbs, and set expressions in both languages. The analysis reveals that while both languages share common thematic domains — family solidarity, intergenerational transmission, and parent-child relations — they encode them through culturally distinct imagery. English phraseology foregrounds individual autonomy and pragmatic family values; Uzbek phraseological stock consistently reflects collectivist orientations, Islamic ethical imperatives, and patriarchal social organisation. The findings contribute to comparative phraseology, linguoculturology, and translation studies.